Targeting Apoptosis Signaling Pathways for Anticancer Therapy - Fulda, Simone (Frontiers in Oncology, 2011)
Treatment approaches for cancer, for example chemotherapy, radiotherapy or immunotherapy, primarily act by inducing cell death in cancer cells. Consequently, the inability to trigger cell death pathways or alternatively, evasion of cancer cells to the induction of cell death pathways can result in resistance of cancers to current treatment protocols. Therefore, in order to overcome treatment resistance a better understanding of the underlying mechanisms that regulate cell death and survival pathways in cancers and in response to cancer therapy is necessary to develop molecular-targeted therapies. This strategy should lead to more effective and individualized treatment strategies that selectively target deregulated signaling pathways in a tumor type- and patient-specific manner.